INTERCURRENT PRESCRIPTION: CRITICAL ANALYSIS AND REFLECTIONS IN THE TAX EXECUTION PROCESS (REMUNOM, 2024)
This work aims to analyze intercurrent prescription in the context of the tax enforcement process, highlighting its concept, occurrence and implications. Initially, we will address the theoretical foundations of prescription and intercurrent prescription, examining how these institutes manifest themselves within the scope of tax legislation. Next, we will explore the relationship between intercurrent prescription and the civil and tax enforcement process, considering the constitutional aspects that guide these procedures. The procedural regime of prescription will also be discussed according to the Tax Execution Law and the Civil Procedure Code, highlighting the particularities and possible normative conflicts. Furthermore, we will analyze the jurisprudence related to the topic, with an emphasis on the repercussion of Resp 1340.553/RS for the tax enforcement process. Finally, the practical implications of intercurrent prescription in the context of tax enforcement will be presented, providing reflections on its application and relevance to the legal system.